INVOLVING STUDENTS WITH DISABILITIES IN EDUCATION (Scientific journal of the Fergana State University, 2023)
This article covers the topic of social protection and educational achievements of children with special educational needs in the Republic of Uzbekistan. The article emphasizes the importance of inclusive education, which allows children with different needs to learn together with their peers and adapt to society. The importance of creating conditions for inclusive education and its positive impact on the future of children with special needs in society is highlighted.